2017
DOI: 10.18001/trs.3.2.12
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of the Food and Drug Administration as a Tobacco Regulator

Abstract: Objectives The U. S. Food and Drug Administration (FDA) now has regulatory authority over all tobacco products. Little is known about public awareness and perceptions of FDA in their new role as a tobacco regulator. This research utilizes focus groups to examine perceptions of FDA as a tobacco regulator so that FDA can better communicate with the public about this role. Methods We conducted 6 focus groups in 2014 among a diverse sample of smokers and non-smokers. Participants were asked if they had heard of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…A more recent study by Kowitt et al, (2017) found that only 43% of US adults reported trust in the federal government and that trust in FDA was moderate (62%) but lower than trust in the CDC (65%) [ 5 ]. Research also shows low public awareness of FDA’s tobacco regulatory and communication roles [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…A more recent study by Kowitt et al, (2017) found that only 43% of US adults reported trust in the federal government and that trust in FDA was moderate (62%) but lower than trust in the CDC (65%) [ 5 ]. Research also shows low public awareness of FDA’s tobacco regulatory and communication roles [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, motivated tobacco users may engage in information seeking behaviors to find information relevant to tobacco product harm and risk, leading to exposure to FDA regulatory policies. Because studies have shown consumer beliefs and support for the role of the FDA in regulating tobacco products (Jarman et al, 2017; Boynton et al, 2016), it is important to communicate to the public that FDA tobacco regulation does not imply that any tobacco product is safe. Tobacco products cannot be regulated using standards of product efficacy and safety as they are not considered therapeutics or drug devices (Hamburg & Sharfstein, 2009; Federal Food, Drug, and Cosmetic Act, 1938; Greene & Podolsky, 2012; Kefauver Harris Amendment (Drug Amendments of 1962), 1962); rather, tobacco products are regulated under population health standards for both tobacco users and non-users.…”
Section: Discussionmentioning
confidence: 99%
“…These results are aligned with previous findings from an earlier study using 2012/2013 HINTS data which showed that uncertainty about FDA regulation was associated with uncertainty about the harmfulness of tobacco products (Kaufman et al, 2011). In addition, findings from a recent focus group study indicated consumer approval of FDA’s role in tobacco regulation and support for the role of FDA in communicating tobacco product risks (Jarman et al, 2017). Utilizing these findings, communication strategies could focus on areas where individuals’ perceptions may be unclear or inaccurate (e.g., correcting misperceptions that the FDA regulates tobacco products under standards of safety and efficacy while raising consumer awareness of population health standards under which FDA regulates tobacco products).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, research on awareness and trust in the FDA’s role as a tobacco regulator has focused on predominantly white population samples. 8-11 In a focus group study with 41 US adults (24% self-identified as Black), Jarman et al 8 found that most participants were unaware of the FDA’s authority to regulate tobacco and expressed only partial trust in the FDA. Additionally, in a nationally representative survey of 4758 US adults (19.6% self-identified as Black), Schmidt et al 10 found that credibility perceptions of the FDA were higher among white respondents as compared to Black respondents.…”
mentioning
confidence: 99%